2015
DOI: 10.1136/bmjopen-2014-007166
|View full text |Cite
|
Sign up to set email alerts
|

National survey of physicians to determine the effect of unconditional incentives on response rates of physician postal surveys

Abstract: ObjectivesPhysicians are a commonly targeted group in health research surveys, but their response rates are often relatively low. The goal of this paper was to evaluate the effect of unconditional incentives in the form of a coffee card on physician postal survey response rates.DesignFollowing 13 key informant interviews and eight cognitive interviews a survey questionnaire was developed.ParticipantsA random sample of 534 physicians, stratified by physician group (geriatricians, family physicians, emergency ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…Beyond survey mode, a number of other survey design factors associated with increased HCP survey response rates have been reported in the literature (Abdulaziz et al, ; Burke & Hodgins, ; Martins et al, ; Nicholls et al, ; Pit et al, ). Most have been adapted from the Dillman's Tailored Design Method and are classified as either design strategies or incentives (Dillman, Smyth, & Christian, ).…”
Section: Surveying Healthcare Providersmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond survey mode, a number of other survey design factors associated with increased HCP survey response rates have been reported in the literature (Abdulaziz et al, ; Burke & Hodgins, ; Martins et al, ; Nicholls et al, ; Pit et al, ). Most have been adapted from the Dillman's Tailored Design Method and are classified as either design strategies or incentives (Dillman, Smyth, & Christian, ).…”
Section: Surveying Healthcare Providersmentioning
confidence: 99%
“…Larger monetary incentives (e.g., $50) generally yield higher response rates than smaller ones (e.g., $20; Keating, Zastavsky, Goldstein, West, & Ayanian, ; VanGeest & Johnson, ). Abdulaziz et al () found that even a $10 gift card resulted in a significant increase in response rates (from 51.3% to 62.7%). Although raffles or prize drawings have been frequently used as incentives because they are easy to implement, relatively inexpensive and considered a fixed‐cost option, their impact on participation rates has been small and often comparable to not offering any incentive (Dykema et al, ).…”
Section: Surveying Healthcare Providersmentioning
confidence: 99%
“…Nevertheless, the link between these recommendations and higher response rates remains to be further elucidated, as several studies conducted with physicians have given inconsistent findings. Some have shown that questionnaire length 36 and the use of incentives 37,38 have a threshold effect on response rate, but others have suggested that reducing questionnaire length [39][40][41] and using incentives 40,41 does not make a significant difference. Moreover, a randomized trial conducted with questionnaires on a topic similar to ours, in a comparable population, showed no significant difference in response rate between a longer questionnaire (54 questions) and a shorter questionnaire (27 questions).…”
Section: Structural Changesmentioning
confidence: 99%
“…Although the response rate was relatively low, respondent characteristics were similar to those of the overall population, minimizing the potential for response bias. The modified Dillman method used in this study provided a practical guideline for improving the response rate, although future work is needed to examine strategies for improving the trend of lower response rates among primary care physicians (37)(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%